Effects of Zinc and Menthol-Based Diets on Co-Selection of Antibiotic Resistance among E. coli and Enterococcus spp. in Beef Cattle - Sarah A. Murray; Raghavendra G. Amachawadi; Keri N. Norman; Sara D. Lawhon; Tiruvoor G. Nagaraja; James S. Drouillard; Harvey M. Scott (Animals, 2021)
Antibiotic resistance represents a growing crisis in both human and veterinary medicine. We evaluated the use of antibiotic alternatives—heavy metals and essential oils—in beef cattle feeding, and their effects on Gram-negative and Gram-positive bacteria. In this randomized controlled field trial, we measured the impact of supplemental zinc and menthol on antibiotic resistance among commensal enteric bacteria of feeder cattle. Fecal suspensions were plated onto plain- and antibiotic-supplemented MacConkey and m-Enterococcus agar for quantification of total and antibiotic-resistant Escherichia coli and Enterococcus spp., respectively. Temporal effects on overall E. coli growth were significant (p < 0.05), and menthol was associated with decreased growth on tetracycline-supplemented agar. Zinc was associated with significant increases in growth on erythromycin-supplemented m-Enterococcus agar. Cattle fed zinc exhibited significantly higher levels of macrolide resistance among fecal enterococci isolates.